Implementation Of Problem-Based Learning To Improve Student Learning Outcomes - Siti Sukowati Wanafaktu Miruki; M. Bagus Ardianto; Anggun Wulandari (SCHOOLAR: Social and Literature Study in Education, 2025)
This study aims to implement and evaluate the effectiveness of the Problem-Based Learning Model (PBL) in improving the learning outcomes of class X Office Management (MP) 1 students on the material of social interaction and dynamics at private vocational secondary schools 1 Jombang. The research method used is a quantitative approach with a pretest-posttest design. The research sample consisted of 34 students who were all used as respondents through saturated sampling techniques. The results of the study showed that there was a significant increase in student learning outcomes after the implementation of the PBL model. The average pretest score of students before problem-based learning was 73, while the average posttest score increased to 82. In addition, students' responses to this learning model were also very positive, with increased motivation and involvement in the learning process. Based on the results of the study, it can be concluded that the implementation of the PBL model is effective in improving student learning outcomes. Therefore, it is recommended that teachers apply this method more often to improve student activity and understanding. In addition, further research is recommended to consider the characteristics and needs of students so that learning can run more optimally.